Deep Hydrogenation Saturated Catalysts for Residue Oil, Their Preparation Methods and Applications
Patent Information
- Application Number
- CN202510454660.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2026-10-20
Smart Images

Figure BDA0005355146760000201 
Figure BDA0005355146760000211 
Figure BDA0005355146760000221
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of residue hydrotreating catalysts, specifically to a deep hydrotreating saturated catalyst for residue oil, its preparation method, and its application. Background Technology
[0002] Fixed-bed residue hydrotreating and catalytic cracking combined technology is one of the most efficient technical routes supporting the transformation of refineries into chemical plants. This technology route can help refineries achieve low-cost transformation to chemical plants using existing equipment. It features strong feedstock adaptability, short process, low investment, and maximizing chemical product production with minimal feedstock consumption. It can simultaneously produce ethylene, propylene, and light aromatics (BTX), adapting to both high and low oil prices and flexibly responding to cyclical changes in the refining and chemical markets. Existing research shows that the properties and hydrocarbon composition of hydrotreated residue have a crucial impact on the chemical yield of catalytic cracking. The higher the hydrogen content and saturated hydrocarbon content of the hydrotreated residue, the higher the yield of low-carbon olefins in the catalytic cracking unit. Deep hydrotreating catalysts for producing high-quality catalytic cracking feedstock can provide subsequent catalytic cracking units with cracking feedstocks of high hydrogen content and low aromatic content, improving propylene yield. This is the key to maximizing chemical feedstock production with fixed-bed residue hydrotreating and catalytic cracking combined technology.
[0003] The development of new catalytic materials is the foundation for improving catalyst performance. Support materials need to have suitable pore size to provide diffusion channels for reactant molecules, while having a large specific surface area to promote the dispersion of active metals on the support surface.
[0004] Patent application CN113649016A describes a process where alumina, metatitanic acid, and a solvent are mixed, high-energy ball-milled, shaped, dried, and calcined to obtain a titanium oxide-alumina support. The titanium oxide-alumina composite support is then impregnated with a solution containing molybdenum and cobalt or nickel, followed by drying and calcination to obtain a hydrogenation catalyst. The hydrogenation catalyst prepared by this method exhibits advantages such as high low-temperature activity, as well as good hydrogenation activity and stability at high space velocities.
[0005] Patent application CN109833891A discloses a heavy distillate oil hydrotreating catalyst and its application using mesoporous TiO2-Al2O3 as a support. A mesoporous alumina precursor is prepared using a template-directed method. Titanium oxide, titanium isopropoxide, or tetrabutyl titanate is then introduced into the precursor solution. After crystallization and drying, a mesoporous TiO2-Al2O3 precursor is obtained. This precursor is mixed with alumina, an extrusion aid, and phosphate, extruded into strips, and then dried and calcined to obtain a phosphorus-modified TiO2-Al2O3 support. The catalyst's active components include Group VIB metal oxides, Group VIII oxides, and Group VA oxides. This method can prepare a mesoporous TiO2-Al2O3 support, effectively improving the catalyst's desulfurization and denitrification capabilities.
[0006] The above methods are complex and discontinuous in preparing titanium oxide-alumina composite oxide supports. The methods for introducing TiO2 mostly involve titanium-containing organic reagents, which are costly and unsuitable for industrial production. Furthermore, when the support is used for deep hydrogenation of residue oil, the catalyst activity still needs to be improved. Summary of the Invention
[0007] The purpose of this invention is to overcome the problems existing in the prior art and provide a saturated catalyst for deep hydrogenation of residue oil, its preparation method and application, which has high activity for deep hydrogenation of residue oil.
[0008] To achieve the above objectives, a first aspect of the present invention provides a saturated catalyst for deep hydrotreating of residual oil, wherein the catalyst comprises a composite oxide support and an active metal supported on the composite oxide support, the composite oxide support containing alumina and titanium oxide, the titanium oxide existing in an amorphous form; the active metal comprises Group VIII and Group VIB metal elements; the pore concentration A of the support is 0.65-2; pores with a diameter of 4-13 nm account for 86-100% of the total pore volume in the composite oxide support; when the catalyst is measured by hydrogen-programmed temperature rise, the ratio S of the reduction peak at 300-500℃ to the reduction peak at 650-850℃ is 3-50; wherein, based on the total amount of the catalyst, the carbon content on the catalyst, in elemental terms, is 0.1-10% by weight.
[0009] Preferably, in the composite oxide carrier, pores with a diameter of 4-13 nm account for 88-96% of the total pore volume.
[0010] Preferably, when the catalyst is measured by hydrogen-programmed temperature rise, the ratio S of the reduction peak at 300-500℃ to the reduction peak at 650-850℃ is 3.5-10.
[0011] A second aspect of the present invention provides a method for preparing deeply hydrogenated saturated residue oil, wherein the method includes the following steps:
[0012] (1) A gelling reaction is carried out between an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum to obtain a solid gelling product;
[0013] (2) In the presence of a precipitant, the solid gelling product is subjected to an aging reaction to obtain titanium-containing pseudoboehmite;
[0014] (3) The titanium-containing pseudoboehmite is optionally shaped, and then subjected to a first drying and a first calcination to obtain a composite oxide carrier, wherein the composite oxide contains aluminum oxide and titanium oxide, and the titanium oxide exists in an amorphous form;
[0015] (4) Introduce active metals and organic matter into a support, and then perform a second drying and a second calcination. The active metals include Group VIII metals and Group VIB metals. The second calcination is carried out under nitrogen and / or an inert atmosphere.
[0016] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the method described in the second aspect in the deep hydrotreating of residue oil.
[0017] The saturated catalyst for deep hydrotreating of residue oil provided by this invention uses a composite oxide of alumina and titanium dioxide with high pore concentration and a specific effective pore size ratio as a support. The catalyst has a high effective pore size ratio and contains a specific amount of carbon to coat or isolate the active phase, so as to avoid the decrease in stability and growth caused by aggregation during long-term operation. This improves the catalytic activity of deep hydrotreating of residue oil, enhances desulfurization and carbon removal performance, and increases the H content and propylene yield of the product.
[0018] The residue deep hydrosaturation catalyst provided by the present invention, in a preferred embodiment, can achieve a high pore concentration while maintaining a low titanium oxide content in the composite oxide support.
[0019] The method provided by this invention combines co-precipitation and aging reactions. A titanium source is introduced into an acidic solution, allowing titanium to be more uniformly dispersed in the composite oxide support. Furthermore, the aging temperature is controlled to be higher than the gelation temperature, resulting in smaller alumina-titanium oxide composite oxide grain sizes. This improves the pore distribution ratio and pore concentration of 4-13 nm effective pores in the composite oxide support. Introducing organic matter as a carbon source into the catalyst preparation can coat or isolate the active phase, preventing it from becoming unstable and growing due to aggregation during long-term operation. Detailed Implementation
[0020] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0021] The first aspect of this invention provides a saturated catalyst for deep hydrotreating of residual oil, wherein the catalyst comprises a composite oxide support and an active metal supported on the composite oxide support, the composite oxide support containing alumina and titanium oxide, the titanium oxide existing in an amorphous form; the active metal comprises Group VIII and Group VIB metal elements; the pore concentration A of the support is 0.65-2; in the composite oxide support, pores with a diameter of 4-13 nm account for 86-100% of the total pore volume; when the catalyst is measured by hydrogen-programmed temperature rise, the ratio S of the reduction peak located at 300-500℃ to the reduction peak located at 650-850℃ is 3.5-10; wherein, based on the total amount of the catalyst, the carbon content on the catalyst, in elemental terms, is 0.1-10% by weight.
[0022] The saturated catalyst for deep hydrotreating of residue oil provided by this invention uses a composite oxide of alumina and titanium dioxide with high pore concentration and a specific effective pore size ratio as a support. The catalyst has a high effective pore size ratio and contains a specific amount of carbon to coat or isolate the active phase, so as to avoid the decrease in stability and growth caused by aggregation during long-term operation. This improves the catalytic activity of deep hydrotreating of residue oil, enhances desulfurization and carbon removal performance, and increases the H content and propylene yield of the product.
[0023] In this invention, an SAP2420 automated adsorption analyzer manufactured by Micromerities Instruments, Inc. (USA) was used to determine the specific surface area and pore structure of the carrier using the N2 static low-temperature adsorption capacity method. Before testing, the sample was degassed under vacuum at 300℃ and 1.33 Pa for 4 hours, then contacted with the N2 adsorbate at 196℃ to reach static adsorption equilibrium. The amount of N2 adsorbed by the sample was calculated from the difference between the N2 inlet gas rate and the amount remaining in the gas phase after adsorption. The surface area was calculated using the BET formula. The pore concentration was defined as the highest DV value (DV) in the BET pore size distribution-DV curve. MAX The ratio of the pore size to the full width at half maximum (FWHM), i.e., the pore size concentration A = DV. MAX / FWHM.
[0024] In this invention, the H2-TPR (hydrogen-programmed temperature reduction) of the catalyst (oxidized catalyst) was determined using an AutoChem II 2920 multifunctional adsorption analyzer from Micromeritics, USA. The specific conditions were as follows: 0.20 g of 40-60 mesh catalyst was packed into a U-shaped quartz tube, and the temperature was increased to 50°C at a rate of 2°C / min in argon gas at a flow rate of 50 mL / min. The sample was pretreated for 10 min, then switched to Ar carrier gas containing 10% H2 by volume at a flow rate of 50 mL / min. After baseline stabilization, the temperature was increased to 1000°C at a rate of 10°C / min. The carrier gas passed through the reactor and then into a cold trap to condense the water generated during the reduction process. Simultaneously, a thermal conductivity detector was used to detect the signal, obtaining the TPR spectrum of the sample. The ratio S of the reduction peak at 300-500°C to the reduction peak at 650-850°C was then calculated based on the TPR spectrum.
[0025] In this invention, the form in which titanium oxide exists is determined by XRD.
[0026] In this invention, the carbon content in the catalyst is determined by infrared absorption. The sample and the co-solvent are placed in a high-frequency induction furnace and oxygen is introduced for combustion. The generated CO2 gas flows through the infrared absorption cell and absorbs infrared energy. The C content can be obtained from the change in energy.
[0027] In this invention, preferably, the pore concentration A of the composite oxide support is 0.75-2, for example, it can be 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, or 2. The advantage of this preferred embodiment is that the effective pores are concentrated within the size range required for the molecular reaction, resulting in high utilization of active metals and high catalyst activity. In contrast, in existing technologies, the pore concentration is typically in the range of 0.1-0.5, resulting in a low proportion of effective pores and low utilization of active metals, which is detrimental to the hydrogenation reaction.
[0028] In this invention, preferably, pores with a diameter of 4-13 nm account for 88-96% of the total pore volume in the composite oxide support. The advantage of this preferred embodiment is that the effective pores are concentrated within the size range required for molecular reactions, resulting in high utilization of active metals and high catalyst activity. Typically, in existing technologies, pores with a diameter of 4-13 nm account for 40-80% of the total pore volume, resulting in a low proportion of effective pores and low utilization of active metals, which is detrimental to improving catalyst activity.
[0029] In this invention, preferably, pores with a diameter of 6-10 nm account for 60-100% of the total pore volume in the carrier composite oxide, more preferably 70-98%. The advantage of this preferred embodiment is that the effective pore distribution is more concentrated within the size range required for molecular reactions, which is beneficial for the diffusion of reacting molecules to the active centers and avoids waste of active metals.
[0030] In this invention, preferably, when the catalyst is measured by hydrogen-programmed temperature rise, the ratio S of the reduction peak at 300-500℃ to the reduction peak at 650-850℃ is 3.5-10, for example, it can be 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, or 10. The advantage of this preferred embodiment is that while the metal sulfidation degree is high, the aggregation of active metal and the utilization rate are not reduced due to the weakened interaction between the metal and the support.
[0031] In this invention, preferably, the specific surface area of the composite oxide carrier is 180-400 m². 2 / g, preferably 200-300m 2 / g.
[0032] In this invention, preferably, the pore volume of the composite oxide support is 0.4-1.3 mL / g, more preferably 0.5-1.2 mL / g.
[0033] In this invention, preferably, the average pore size of the composite oxide support is 4-16 nm, more preferably 5-13 nm. The advantage of this preferred embodiment is that it facilitates intramolecular diffusion to the active metal.
[0034] In this invention, preferably, based on the total amount of the composite oxide support, the alumina content is 80-95% by weight, and the titanium oxide content is 5-20% by weight; more preferably, based on the total amount of the composite oxide support, the alumina content is 85-90% by weight, and the titanium oxide content is 10-15% by weight. While ensuring a low titanium oxide content, the composite oxide support can maintain high pore volume and high specific surface area, thereby improving the activity of the catalyst.
[0035] In this invention, the contents of aluminum oxide and titanium oxide in the composite oxide carrier were measured using a Rigaku Electric Industries, Ltd. 3271 X-ray fluorescence spectrometer.
[0036] In this invention, preferably, based on the total amount of the catalyst and calculated as oxides, the content of the Group VIII metal element is 0.5-10% by weight, preferably 1.5-5% by weight, and the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight.
[0037] In this invention, the content of each component in the catalyst is determined by XRF fluorescence analysis.
[0038] In this invention, preferably, the Group VIII metal element is cobalt and / or nickel.
[0039] In this invention, preferably, the Group VIB metal element is molybdenum and / or tungsten.
[0040] In this invention, preferably, the catalyst further contains an auxiliary agent, and more preferably, the auxiliary agent is selected from at least one of phosphorus, silicon, magnesium and fluorine.
[0041] In this invention, preferably, the content of the auxiliary agent is 0.1-10% by weight, based on the total amount of the catalyst and calculated as oxides.
[0042] In this invention, preferably, the carbon content on the catalyst, calculated as an element, is 0.2-0.9% by weight, based on the total amount of the catalyst.
[0043] A second aspect of the present invention provides a method for preparing deeply hydrogenated saturated residue oil, wherein the method includes the following steps:
[0044] (1) A gelling reaction is carried out between an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum to obtain a solid gelling product;
[0045] (2) In the presence of a precipitant, the solid gelling product is subjected to an aging reaction to obtain titanium-containing pseudoboehmite;
[0046] (3) The titanium-containing pseudoboehmite is optionally shaped, and then subjected to a first drying and a first calcination to obtain a composite oxide carrier, wherein the composite oxide carrier contains aluminum oxide and titanium oxide, which exist in an amorphous form;
[0047] (4) Introduce active metals and organic matter into a support, and then perform a second drying and a second calcination. The active metals include Group VIII metals and Group VIB metals. The second calcination is carried out under nitrogen and / or an inert atmosphere.
[0048] The method provided by this invention combines co-precipitation and aging reactions. A titanium source is introduced into an acidic solution, allowing titanium to be more uniformly dispersed in the composite oxide support. Furthermore, the aging temperature is controlled to be higher than the gelation temperature, resulting in smaller alumina-titanium oxide composite oxide grain sizes. This improves the pore distribution ratio and pore concentration of 4-13 nm effective pores in the composite oxide support. Moreover, the method of this invention ensures high pore concentration in the composite oxide support while producing a catalyst with high metal sulfidation, and prevents the aggregation and utilization rate of active metals from decreasing due to weakened interactions between the metal and the support.
[0049] In this invention, preferably, in step (1), the acidic aluminum-containing and titanium-containing solutions are prepared by mixing a titanium-containing compound solution with an acidic aluminum solution. This invention improves the dispersibility of titanium oxide by introducing a titanium source into the acidic solution, allowing titanium to be more uniformly dispersed in the composite oxide carrier.
[0050] In this invention, preferably, the titanium-containing compound is selected from at least one of titanium oxysulfate, titanium sulfate, and metatitanic acid.
[0051] In this invention, the amount of titanium-containing compound used is not particularly limited, as long as the concentration requirement of the titanium-containing compound solution is met. Preferably, the concentration of the titanium-containing compound solution, calculated as titanium oxide, is 5-80 g / L, more preferably 10-80 g / L.
[0052] In this invention, the type of acidic aluminum solution is not particularly limited; any acidic aluminum salt solution is applicable. Preferably, the acidic aluminum solution is selected from at least one of aluminum sulfate solution, aluminum nitrate solution, and aluminum chloride solution.
[0053] In this invention, preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as aluminum oxide, is 35-120 g / L, for example, it can be 35 g / L, 45 g / L, 55 g / L, 65 g / L, 75 g / L, 85 g / L, 95 g / L, 105 g / L, 115 g / L or 120 g / L.
[0054] In this invention, preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as titanium oxide, is 5-80 g / L, for example, it can be 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L or 80 g / L.
[0055] In this invention, preferably, in step (1), the concentration of the aluminum-containing alkaline solution, calculated as alumina, is 20-300 g / L, for example, it can be 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L, 100 g / L, 250 g / L, 260 g / L, 270 g / L, 280 g / L, 290 g / L, or 300 g / L.
[0056] In this invention, the concentration of the aluminum-containing alkaline solution, calculated as alumina, is 20-200 g / L, preferably 35-120 g / L, for example, it can be 35 g / L, 45 g / L, 55 g / L, 65 g / L, 75 g / L, 85 g / L, 95 g / L, 105 g / L, 115 g / L or 120 g / L.
[0057] In this invention, preferably, the amounts of the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are such that, based on the total amount of the composite oxide carrier, the content of aluminum oxide is 70-99% by weight, preferably 75-96% by weight, and the content of titanium oxide is 1-30% by weight, preferably 4-25% by weight.
[0058] In this invention, the temperature of the aging reaction is 5-50°C higher than the temperature of the gelation reaction, preferably 10-30°C higher; the advantage of this preferred embodiment is that it promotes the growth of boehmite particles and ensures that the carrier has a higher pore concentration.
[0059] In this invention, the method of gelation reaction is not particularly limited. Preferably, in step (1), the gelation reaction is carried out continuously or intermittently, preferably continuously. Continuous gelation is more conducive to controlling the pH during the gelation reaction process, effectively improving the quality of the titanium dioxide-alumina composite oxide.
[0060] According to a preferred embodiment of the present invention, the continuous gelation reaction process of the present invention includes: pre-entering a certain amount of deionized water into a gelation tank, and introducing the acidic solution and / or alkaline aluminum-containing solution from the top of the gelation tank, so that the acidic solution and / or alkaline aluminum-containing solution are mixed to form a gel, and the slurry generated by the gelation reaction continuously flows out of the gelation tank, keeping the liquid level in the gelation tank constant.
[0061] In this invention, the conditions for the gelation reaction are not particularly limited. Preferably, in step (1), the conditions for the gelation reaction include: a temperature of 50-70°C and a pH value of 4-7.
[0062] In this invention, the type of precipitant is not particularly limited, and any alkaline compound conventionally defined in the art can be used in this invention. Preferably, in step (2), the precipitant is selected from alkali metal compounds, and more preferably from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.
[0063] In this invention, the conditions for the aging reaction are not particularly limited. Preferably, in step (2), the conditions for the aging reaction include: a temperature of 60-98°C, a time of 4-9 hours, and a pH value of 7-11; more preferably, in step (2), the conditions for the aging reaction include: a temperature of 70-95°C, a time of 5-8 hours, and a pH value of 7.5-10.
[0064] According to the present invention, after the aging treatment, step (2) further includes solid-liquid separation of the aged product to obtain the aging reaction product. In the present invention, the solid-liquid separation is a conventional operation in the art, specifically, for example, it can be at least one of sedimentation, filtration and centrifugation.
[0065] According to the present invention, preferably, step (2) further includes washing the aging reaction product. In the present invention, the washing operation is a conventional operation in the art, which only requires reducing the content of impurity ions in the aging reaction product, for example, so that the sodium oxide content in the material obtained after calcining the titanium-containing boehmite is less than 0.1 wt%, preferably less than 0.06 wt%, and more preferably 0.01-0.05 wt%.
[0066] In this invention, step (3) optionally means that during the mixing and molding process described in step (3), a glue solvent and an extrusion aid may be added, or no glue solvent and an extrusion aid may be added.
[0067] In this invention, the type of extrusion aid is not particularly limited, and any extrusion aid conventionally defined in the art is applicable to this invention. Preferably, the extrusion aid can be guar gum powder or cellulose, which can be selected by those skilled in the art according to conventional methods.
[0068] In this invention, the type of adhesive solvent is not particularly limited, and adhesive solvents conventionally defined in the art are all applicable to this invention. Preferably, the adhesive solvent can be nitric acid, citric acid, or hydrochloric acid, and those skilled in the art can select according to conventional methods.
[0069] The present invention does not impose any particular limitation on the amount of the adhesive solvent and the extrusion aid, and the amounts can be selected in accordance with conventional methods in the art to ensure smooth subsequent molding.
[0070] In this invention, water may or may not be added during the mixing process described in step (3). This invention does not impose any particular limitation on the amount of water used, as long as the subsequent molding process is successful.
[0071] The present invention does not particularly limit the molding method described in step (3). Commonly used molding methods in the field can be adopted, such as at least one of extrusion molding, spray molding, roll forming and sheet forming, with extrusion molding being preferred.
[0072] In this invention, the conditions for the first drying are not particularly limited, and those skilled in the art can adjust them according to actual needs.
[0073] In this invention, the selection range for the conditions of the first roasting is relatively wide. Preferably, in step (3), the conditions for the first roasting include: a temperature of 300-800℃ and a time of 1-6h.
[0074] In this invention, preferably, the method does not use organic titanium-containing reagents. The advantage of this preferred embodiment is that it facilitates the uniform dispersion of titanium in the composite oxide support.
[0075] In this invention, the conditions for the second drying are not particularly limited, and those skilled in the art can adjust them according to actual needs.
[0076] In this invention, the selection range of the conditions for the second roasting is relatively wide. Preferably, in step (4), the conditions for the second roasting include: a temperature of 100-700℃ and a time of 1-6h; preferably, in step (4), the conditions for the second roasting include: a temperature of 200-700℃ and a time of 2-4h.
[0077] In this invention, the type of inert atmosphere is not particularly limited; for example, argon, helium, neon, etc.
[0078] The present invention does not particularly limit the method for introducing the active metal, and various methods conventionally used in the art can be employed, such as impregnation and co-precipitation. Preferably, the active metal is introduced onto the support using the impregnation method.
[0079] In this invention, preferably, the method includes: impregnating a composite oxide support in an impregnation solution containing a compound of a Group VIII metal element and a Group VIB metal element, followed by a second drying and a second calcination.
[0080] The present invention does not specifically limit the method of impregnation. The method of impregnation can be impregnation with excess liquid or impregnation with equal volume, depending on the amount of impregnation liquid used.
[0081] In this invention, preferably, the amounts of Group VIII and Group VIB metal elements are such that, based on the total amount of the catalyst and in terms of oxides, the content of the Group VIII metal element is 0.5-10% by weight, preferably 1.5-5% by weight; and the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight.
[0082] In this invention, preferably, the Group VIII metal element is cobalt and / or nickel.
[0083] In this invention, preferably, the Group VIB metal element is molybdenum and / or tungsten.
[0084] In this invention, preferably, step (4) further includes: introducing an auxiliary agent, wherein the auxiliary agent is preferably selected from at least one of phosphorus, silicon, magnesium and fluorine.
[0085] In this invention, the amount of the additive is such that, based on the total amount of the catalyst, the content of the additive, calculated as oxide, is 0.1-10% by weight.
[0086] In this invention, preferably, in step (4), the amount of organic matter used is 0.1-10g based on carbon elements, relative to 100g of carrier, for example, it can be 0.1g, 0.5g, 1g, 1.5g, 2g, 2.5g, 3g, 3.5g, 4g, 4.5g, 5g, 5.5g, 6g, 6.5g, 7g, 7.5g, 8g, 8.5g, 9g, 9.5g, or 10g.
[0087] In this invention, there is no particular limitation on the timing of the introduction of the auxiliary agent. For example, it can be introduced together with compounds containing Group VIII metal elements and Group VIB metal elements, or it can be introduced separately, but it is preferred to introduce them together. For example, the auxiliary agent compound can be prepared together with compounds containing Group VIII metal elements and Group VIB metal elements to prepare the impregnation solution.
[0088] The present invention allows for a wide range of choices of compounds containing Group VIII metal elements, which can be conventional choices in the art. Preferably, the compounds containing Group VIII metal elements are selected from at least one of the nitrates, acetates, carbonates, chlorides, and soluble complexes of Group VIII metal elements, such as cobalt nitrate, nickel nitrate, nickel acetate, cobalt acetate, cobalt chloride, nickel chloride, cobalt carbonate, nickel carbonate, cobalt citrate, and nickel citrate.
[0089] The present invention allows for a wide range of choices of compounds containing the Group VIB metal elements, which can be conventional choices in the art. Preferably, the compounds containing the Group VIB metal elements are selected from at least one of molybdates, tungstates, metatungstates, and ethyl metatungstates.
[0090] The present invention allows for a wide range of choices of compounds for the adjuvants. Preferably, the adjuvant compound can be phosphoric acid.
[0091] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the method described in the second aspect in the deep hydrotreating of residue oil.
[0092] In this invention, the conditions for deep hydrotreating of residual oil are not particularly limited. Preferably, the hydrotreating conditions include: a reaction temperature of 200-420℃, more preferably 220-400℃, a pressure of 2-18 MPa, and a liquid hourly space velocity of 0.1-10 h⁻¹. -1 Preferably 0.15-6 hours -1 The hydrogen-to-oil volume ratio is 50-5000, preferably 50-4000.
[0093] The present invention does not impose any particular limitation on the hydrotreating reaction apparatus when using the hydrotreating catalyst. It can be any reactor that allows the feedstock oil to contact and react with the hydrotreating catalyst under hydrotreating reaction conditions, such as a fixed bed reactor, a slurry bed reactor, a moving bed reactor, or a fluidized bed reactor.
[0094] The present invention will be described in detail below through embodiments. Unless otherwise specified, all raw materials used in the following embodiments are commercially available products.
[0095] In the following examples, unless otherwise specified, % refers to mass%.
[0096] Titanium oxide and aluminum oxide in the composite oxide carrier were analyzed by measuring the characteristic spectral lines of each element using a Rigaku Electric Co., Ltd. 3271 X-ray fluorescence spectrometer. The elemental content of the titanium-aluminum composite oxide was semi-quantitatively analyzed using the external standard method, and the composition of Al2O3, TiO2, SO3, Na2O, etc. in the sample was obtained.
[0097] The specific surface area and pore structure of the carrier were determined using an SAP2420 automated adsorption analyzer manufactured by Micromerities Instruments, USA, employing the static low-temperature adsorption capacity method for N2. Before testing, the sample underwent vacuum degassing at 300℃ and 1.33 Pa for 4 hours, followed by contact with the N2 adsorbate at 196℃ to reach static adsorption equilibrium. The amount of N2 adsorbed by the sample was calculated from the difference between the N2 inlet gas rate and the amount remaining in the gas phase after adsorption. The surface area was calculated using the BET formula. Pore concentration was defined as the highest DV value (DV) in the BET pore size distribution-DV curve. MAX The ratio of the pore size to the full width at half maximum (FWHM), i.e., the pore size concentration A = DV. MAX / FWHM.
[0098] The H2-TPR (hydrogen-programmed temperature reduction) of the catalyst (oxidized catalyst) was determined using an AutoChem II 2920 multi-functional adsorption analyzer from Micromeritics, USA. The specific conditions were as follows: 0.20 g of 40-60 mesh catalyst was packed into a U-shaped quartz tube, and the temperature was increased to 50 °C at a rate of 2 °C / min in argon gas at a flow rate of 50 mL / min. The sample was pretreated for 10 min, then switched to Ar carrier gas containing 10% H2 volume fraction at a flow rate of 50 mL / min. After baseline stabilization, the temperature was increased to 1000 °C at a rate of 10 °C / min. The carrier gas passed through the reactor and then into a cold trap to condense the water generated during the reduction process. Simultaneously, the signal was detected using a thermal conductivity detector to obtain the TPR spectrum of the sample. The ratio S of the reduction peak at 300-500 °C to the reduction peak at 650-850 °C was then calculated based on the TPR spectrum.
[0099] In this invention, the carbon content in the catalyst is determined by infrared absorption. The sample and the co-solvent are placed in a high-frequency induction furnace and oxygen is introduced for combustion. The generated CO2 gas flows through the infrared absorption cell and absorbs infrared energy. The C content can be obtained from the change in energy.
[0100] Example 1
[0101] (1) Add 3L of deionized water to the gelling tank in advance, dissolve titanium oxysulfate in aluminum sulfate solution to obtain an acidic solution containing aluminum and titanium, and pass the acidic solution containing aluminum and titanium and sodium aluminate solution from the top of the gelling tank to mix the acidic solution containing aluminum and titanium and sodium aluminate solution in the gelling tank to carry out the gelling reaction. The slurry after the gelling reaction flows out from the overflow pipe of the gelling tank. The liquid level in the gelling tank remains unchanged. When the pre-added deionized water is replaced by the slurry after the gelling reaction, the slurry collection begins, and then the filter cake (solid gelling product) is obtained by filtration.
[0102] The concentration of sodium aluminate solution (calculated as alumina) was 200 g / L, and the flow rate was 42 g / min; the concentration of titanium oxide in the acidic solution was 12.89 g / L, and the concentration of alumina was 58 g / L. By adjusting the flow rate of the acidic solution to 115-125 g / min, the pH value of the gelation reaction was made 6.3; the temperature of the gelation reaction was 60℃.
[0103] (2) The gelation reaction product is subjected to aging treatment. The aging treatment conditions are pH 9.0, temperature 90℃, and time 6h. The aged product is added to deionized water and pulped to obtain an aged mixture. The concentration of the slurry is 70g / L based on titanium oxide-alumina.
[0104] The aged mixture was sequentially filtered and washed to remove residual sodium and sulfate, and then spray-dried to obtain titanium-containing pseudoboehmite Al. The final composition of Al obtained after calcining at 600°C for 3 hours is listed in Table 1.
[0105] (3) Take 100g of titanium-containing boehmite A1 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 85ml of 1.65% nitric acid aqueous solution and mix evenly. Continue to knead the mixture into a plastic body on a twin-screw extruder and then extrude it into a butterfly strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, it is calcined at 550℃ for 3 hours to obtain composite oxide carrier Z1. The properties of composite oxide carrier Z1 are shown in Table 1. XRD characterization shows that titanium oxide in the carrier exists in an amorphous form.
[0106] (4) Take 100g of composite oxide support Z1, impregnate it for 2 hours with a mixed solution of molybdenum oxide, basic nickel carbonate, phosphoric acid and 30g / L ethylene glycol with a MoO3 content of 278g / L, a NiO content of 67.1g / L and a P2O5 content of 57.5g / L, dry it at 120℃ for 2 hours, and calcine it at 400℃ in a nitrogen atmosphere for 3 hours to obtain catalyst C1.
[0107] Comparative Example 1
[0108] According to the method of Example 1, pseudoboehmite S1 was prepared, except that the aluminum sulfate solution in step (1) did not contain titanium oxysulfate.
[0109] (3) Take 100g of pseudoboehmite powder S1 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 90ml of 2.8% nitric acid aqueous solution and continue to knead it into a plastic body on a twin-screw extruder. Then, extrude it into a butterfly strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, it is calcined at 600℃ for 3 hours to obtain carrier DZ1. The properties of carrier DZ1 are shown in Table 1.
[0110] (4) Take 200g of support DZ1, impregnate it for 2 hours with 132ml of a mixed solution of molybdenum oxide, basic nickel carbonate, phosphoric acid and 20g / L citric acid with MoO3 content of 245g / L, NiO content of 50.6g / L and P2O5 content of 59.1g / L, dry it at 120℃ for 2 hours, and calcine it at 400℃ in a nitrogen atmosphere for 3 hours to obtain catalyst DC1.
[0111] Comparative Example 2
[0112] This comparative example uses the preparation method described in the existing technical document (“Effects of the addition of titania onthethermal characterization of alumina-supported palladium”, Journal of Molecular Catalysis A, 2002, 180, 285-291) to prepare titanium dioxide-alumina composite oxide. 20 g of γ-Al₂O₃ (Sinopec Changling Catalyst Co., Ltd.) and 7.74 g of isopropyl titanate were dissolved in propanol, and the solution was measured to 15 mL and stirred thoroughly. Subsequently, γ-Al₂O₃ was dispersed in the above isopropyl titanate solution in isopropanol, dried overnight at 110 °C, and then calcined at 550 °C for 3 hours to obtain titanium dioxide-alumina S₂. The final composition is shown in Table 1.
[0113] Take 100g of support S2 and impregnate it for 2 hours with a mixed solution of molybdenum oxide, basic nickel carbonate, phosphoric acid, and 30g / L ethylene glycol containing 74mL of MoO3 (245g / L), NiO (50.6g / L), P2O5 (59.1g / L), dried it at 120℃ for 2 hours, and calcined it at 400℃ in a nitrogen atmosphere for 3 hours to obtain catalyst DC2.
[0114] Example 2
[0115] The method of Example 1 was followed, except that in step (1), an acidic solution with a different titanium oxide content was used to prepare titanium-containing pseudoboehmite A2. The final composition of A2 obtained after calcining at 600°C for 3 hours is listed in Table 1.
[0116] (3) Take 100g of titanium-containing pseudoboehmite A2 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 105ml of 1% nitric acid aqueous solution and continue to knead it into a plastic body on a twin-screw extruder. Then, extrude it into a butterfly-shaped strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, calcine it at 600℃ for 3 hours to obtain composite oxide carrier Z2. The properties of composite oxide carrier Z2 are shown in Table 1. XRD characterization shows that titanium oxide exists in an amorphous form in the composite oxide carrier.
[0117] (4) Take 100g of composite oxide support Z2, impregnate it for 2 hours with a mixed solution of ammonium molybdate, cobalt nitrate and phosphoric acid with a MoO3 content of 180 g / L, a CoO content of 38 g / L and a P2O5 content of 36 g / L, and glycerol with a 30 g / L, dry it at 120℃ for 2 hours, and calcine it at 400℃ in a nitrogen atmosphere for 3 hours to obtain catalyst C2.
[0118] Example 3
[0119] The method of Example 1 was followed, except that in step (1), an acidic solution with a different titanium oxide content was used to prepare titanium-containing pseudoboehmite A3. The final composition of A3 obtained after calcining at 600°C for 3 hours is listed in Table 1.
[0120] (3) Take 100g of titanium-containing boehmite A3 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 105ml of 2% nitric acid aqueous solution and continue to knead it into a plastic body on a twin-screw extruder. Then, extrude it into a butterfly strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, it is calcined at 600℃ for 3 hours to obtain composite oxide support Z3. The properties of composite oxide support Z3 are shown in Table 1. XRD characterization shows that titanium oxide in the support exists in an amorphous form.
[0121] (4) Take 200g of composite oxide support Z3, impregnate it for 2 hours with 144ml of a mixed solution of ammonium molybdate, cobalt nitrate, phosphoric acid and 30g / L glucose with MoO3 content of 255g / L, CoO content of 61.53g / L and P2O5 content of 52.74g / L, dry it at 120℃ for 2 hours, and calcine it at 400℃ in a nitrogen atmosphere for 3 hours to obtain catalyst C3.
[0122] Example 4
[0123] The method of Example 2 was followed, except that in step (1), an acidic solution with a different titanium oxide content was used to prepare titanium-containing pseudoboehmite A4. The final composition of A4 obtained after calcining at 600°C for 3 hours is listed in Table 1.
[0124] (3) Take 100g of titanium-containing pseudoboehmite A4 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 105ml of 2.5% nitric acid aqueous solution and continue to knead it into a plastic body on a twin-screw extruder. Then, extrude it into a butterfly-shaped strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, calcine it at 600℃ for 3 hours to obtain composite oxide carrier Z4. The properties of composite oxide carrier Z4 are shown in Table 1. XRD characterization shows that titanium oxide in the composite oxide carrier exists in an amorphous form.
[0125] (4) Take 100g of composite oxide support Z4, impregnate it for 2 hours with a mixed solution of ammonium molybdate, cobalt nitrate and phosphoric acid with a MoO3 content of 203 g / L, a CoO content of 42.76 g / L and a P2O5 content of 51.32 g / L, dry it at 120℃ for 2 hours, and calcine it at 400℃ in a nitrogen atmosphere for 4 hours to obtain catalyst C4.
[0126] Comparative Example 3
[0127] Titanium oxide-alumina S3 was obtained by impregnation using the same method as Comparative Example 2. 20 g of γ-Al₂O₃ (Sinopec Changling Catalyst Co., Ltd.) and 15.48 g of isopropyl titanate were dissolved in propanol, and the solution was measured to 15 mL and stirred thoroughly. Subsequently, γ-Al₂O₃ was dispersed in the isopropyl titanate solution in isopropyl alcohol, dried overnight at 110 °C, and then calcined at 550 °C for 3 hours to obtain titanium oxide-alumina S3. The final composition of titanium oxide-alumina S3 is shown in Table 1.
[0128] Take 200g of support S3 and impregnate it for 2 hours with 148 mL of a mixed solution of ammonium molybdate, cobalt nitrate, phosphoric acid, and 25 g / L glucose containing 179.6 g / L MoO3, 42.76 g / L CoO, and 51.32 g / L P2O5. Dry it at 120℃ for 2 hours and calcine it at 500℃ in an argon atmosphere for 3 hours to obtain catalyst DC3.
[0129] Example 5
[0130] (1) Add 3L of deionized water to the gelation tank in advance, and introduce an acidic solution containing aluminum and titanium and a sodium aluminate solution from the top of the gelation tank to mix the acidic solution containing aluminum and titanium and the sodium aluminate solution in the gelation tank to carry out the gelation reaction. The slurry after the gelation reaction flows out from the overflow pipe of the gelation tank. The liquid level in the gelation tank remains unchanged. When the pre-added deionized water is replaced by the slurry after the gelation reaction, the slurry collection begins, and then the filter cake (solid gelation product) is obtained by filtration.
[0131] The concentration of sodium aluminate solution (calculated as alumina) was 210 g / L, and the flow rate was 50 g / min; the concentration of titanium oxide in the acidic solution was 15 g / L, and the concentration of alumina was 48 g / L. The pH value of the gelation reaction was adjusted to 6.5 by adjusting the flow rate of the acidic solution; and the temperature of the gelation reaction was 65℃.
[0132] (2) The gelation reaction product is subjected to aging treatment. The aging treatment conditions are pH 9.5, temperature 95℃, and time 6h. The aged product is added to deionized water and pulped to obtain an aged mixture. The concentration of the slurry is 70g / L based on titanium oxide-alumina.
[0133] The aged mixture was sequentially filtered and washed to remove residual sodium and sulfate, and then spray-dried to obtain titanium-containing pseudoboehmite Al. The final composition of Al obtained after calcining at 600°C for 3 hours is listed in Table 1.
[0134] (3) Take 100g of titanium-containing boehmite A1 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 85ml of 1.65% nitric acid aqueous solution and continue to knead it into a plastic body on a twin-screw extruder. Then, extrude it into a butterfly strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, it is calcined at 600℃ for 3 hours to obtain the composite oxide support Z5. XRD characterization shows that the titanium oxide in the support exists in an amorphous form.
[0135] (4) Take 100g of composite oxide support Z5, impregnate it for 2 hours with a mixed solution of molybdenum oxide, basic nickel carbonate and phosphoric acid and 20g / L ethylene glycol with a MoO3 content of 285g / L, a NiO content of 70.1g / L and a P2O5 content of 58.1g / L, dry it at 120℃ for 2 hours, and calcine it at 400℃ in an argon atmosphere for 3 hours to obtain catalyst C5.
[0136] Example 6
[0137] The method is the same as in Example 1, except that in step (2), the aging temperature is 66°C.
[0138] Example 7
[0139] The method is the same as in Example 1, except that in step (1), the concentration of the titanium-containing compound solution is 8 g / L, calculated as titanium oxide.
[0140] Comparative Example 4
[0141] The method is the same as in Example 1, except that in step (2), the aging temperature is 50°C.
[0142] Comparative Example 5
[0143] The method is the same as in Example 5, except that ethylene glycol is not added in step (4).
[0144] Table 1
[0145]
[0146]
[0147] Test case
[0148] The above examples and comparative examples were used for deep hydrogenation saturation reactions of residue oil.
[0149] The hydrogenation catalysts prepared in the above-mentioned 100 mL examples and comparative examples were crushed into particles with a diameter of 2-3 mm and then pre-sulfurized. The pre-sulfurization conditions included: using Jingmen Changyi No. 1 kerosene containing 5 wt% dimethyl disulfide as the sulfiding oil, and a liquid hourly space velocity (LHSV) of 1.2 h⁻¹ for the sulfiding oil. -1 The hydrogen partial pressure was 14.0 MPa, the hydrogen-to-oil volume ratio was 400, and the reaction was carried out at a constant temperature of 360℃ for 3 hours. Evaluation was then conducted in a 100 mL small fixed-bed reactor (catalyst loading: 100 mL). The feedstock was atmospheric residue oil from Anqing Petrochemical (sulfur content: 1.3 wt%, nitrogen content: 0.42 wt%, carbon residue: 9.1 wt%), and the reaction was carried out at a reaction temperature of 395℃, a hydrogen partial pressure of 14 MPa, and a liquid hourly space velocity (LHSV): 0.5 h⁻¹. -1 Hydrogenation activity performance was tested under the condition of a hydrogen-to-oil volume ratio of 600. The test results after 1500 hours are shown in Table 2.
[0150] The product density in Table 2 was analyzed using the specific gravity bottle method. For specific analytical methods, please refer to standard GB / T2540-1988.
[0151] The H content test method in Table 2 is the elemental analyzer method. For specific analysis methods, please refer to standard SH / T0656-1998(2004).
[0152] The propylene content in the gaseous products of the DCC medium-sized unit was analyzed by gas chromatography, and the propylene yield in Table 2 was then calculated.
[0153] The sulfur content in the feedstock oil sample was determined using the coulombic method (see Petrochemical Analytical Methods RIPP 62-90 for details). The carbon residue content in the feedstock oil sample was determined using the micro-method (see Petrochemical Analytical Methods RIPP 149-90 for details). The nitrogen content in the feedstock oil sample was determined using the chemiluminescence method (see Petrochemical Analytical Methods RIPP SH0704-Z for details).
[0154] Table 2
[0155]
[0156] As can be seen from the table above, the hydrogenation catalyst provided by this invention has better and lower product sulfur content and carbon residue value under the same conditions. The hydrogenation catalyst provided by this invention has higher propylene yield and product hydrogen content under the same conditions. Compared with Example 5, when no organic carbon is introduced into Comparative Example 5, after 1500 hours of long-term operation, the desulfurization and carbon residue removal rates of the catalyst are significantly lower due to the decrease in the stability of the active phase and the aggregation and growth, and the product hydrogen content is lower. Therefore, it is predicted that the propylene yield of the DCC medium-sized unit will be significantly lower than that of Example 5.
[0157] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A saturated catalyst for deep hydrotreating of residual oil, wherein, The catalyst comprises a composite oxide support and an active metal supported on the composite oxide support. The composite oxide support contains alumina and titanium oxide, with the titanium oxide existing in an amorphous form. The active metal comprises Group VIII and Group VIB metal elements. The pore concentration A of the composite oxide support is 0.65-2. In the composite oxide support, pores with a diameter of 4-13 nm account for 86-100% of the total pore volume. When the catalyst is measured by hydrogen-programmed temperature rise, the ratio S of the reduction peak at 300-500℃ to the reduction peak at 650-850℃ is 3-50. Based on the total amount of the catalyst, the carbon content on the catalyst, in elemental terms, is 0.1-10% by weight.
2. The catalyst according to claim 1, wherein, The pore concentration A of the composite oxide support is 0.75-2; Preferably, in the composite oxide carrier, pores with a diameter of 4-13 nm account for 88-96% of the total pore volume; Preferably, in the composite oxide carrier, pores with a diameter of 6-10 nm account for 60-100% of the total pore volume, more preferably 70-98%. Preferably, when the catalyst is measured by hydrogen-programmed temperature rise, the ratio S of the reduction peak at 300-500℃ to the reduction peak at 650-850℃ is 3.5-10.
3. The catalyst according to claim 1 or 2, wherein, The specific surface area of the composite oxide carrier is 180-400 m². 2 / g, preferably 200-300m 2 / g; Preferably, the pore volume of the composite oxide support is 0.4-1.3 mL / g, more preferably 0.5-1.2 mL / g; Preferably, the average pore size of the composite oxide support is 4-16 nm, more preferably 5-13 nm; Preferably, based on the total amount of the composite oxide carrier, the content of alumina is 70-99% by weight, preferably 75-96% by weight, and the content of titanium oxide is 1-30% by weight, preferably 4-25% by weight.
4. The catalyst according to claim 1 or 2, wherein, Based on the total amount of the catalyst, and calculated as oxides, the content of the Group VIII metal element is 0.5-10% by weight, preferably 1.5-5% by weight, and the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight. Preferably, the Group VIII metallic element is cobalt and / or nickel; Preferably, the Group VIB metal element is molybdenum and / or tungsten; Preferably, the catalyst further contains an auxiliary agent, and the auxiliary agent is preferably selected from at least one of phosphorus, silicon, magnesium and fluorine; Preferably, based on the total amount of the catalyst, the content of the auxiliary agent is 0.1-10% by weight, calculated as oxides; Preferably, based on the total amount of the catalyst, the carbon content on the catalyst, expressed as an element, is 0.2-0.9% by weight.
5. A method for preparing a saturated catalyst for deep hydrotreating of residual oil, wherein, The method includes the following steps: (1) A gelling reaction is carried out between an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum to obtain a solid gelling product; (2) In the presence of a precipitant, the solid gelling product is subjected to an aging reaction to obtain titanium-containing pseudoboehmite, wherein the temperature of the aging reaction is higher than the temperature of the gelling reaction. (3) The titanium-containing pseudoboehmite is optionally shaped, and then subjected to a first drying and a first calcination to obtain a composite oxide carrier, wherein the composite oxide carrier contains aluminum oxide and titanium oxide, and the titanium oxide exists in an amorphous form; (4) Introduce active metals and organic matter into a support, and then perform a second drying and a second calcination. The active metals include Group VIII metals and Group VIB metals. The second calcination is carried out under nitrogen and / or an inert atmosphere.
6. The method according to claim 5, wherein, In step (1), the acidic aluminum-containing and titanium-containing solutions are prepared by mixing a titanium-containing compound solution with an acidic aluminum solution; Preferably, the titanium-containing compound is selected from at least one of titanium oxysulfate, titanium sulfate, and metatitanic acid; Preferably, the acidic aluminum solution is selected from at least one of aluminum sulfate solution, aluminum nitrate solution, and aluminum chloride solution; Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as aluminum oxide, is 35-120 g / L. Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as titanium oxide, is 5-80 g / L. Preferably, in step (1), the concentration of the aluminum-containing alkaline solution, calculated as alumina, is 20-300 g / L; Preferably, the amounts of the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are such that, based on the total amount of the composite oxide carrier, the content of aluminum oxide is 70-99% by weight, preferably 75-96% by weight, and the content of titanium oxide is 1-30% by weight, preferably 4-25% by weight.
7. The method according to claim 5 or 6, wherein, The aging reaction temperature is 5-50°C higher than the gelation reaction temperature, preferably 10-30°C higher. Preferably, in step (1), the conditions for the gelation reaction include: a temperature of 50-70°C and a pH value of 4-7.
8. The method according to claim 5 or 6, wherein, In step (2), the precipitant is selected from alkali metal compounds, preferably from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; Preferably, in step (2), the conditions for the aging reaction include: a temperature of 60-98°C, a time of 4-9 hours, and a pH value of 7-11. More preferably, in step (2), the conditions for the aging reaction include: a temperature of 70-95°C, a time of 5-8 hours, and a pH value of 7.5-10.
9. The method according to claim 5 or 6, wherein, In step (3), the conditions for the first roasting include: a temperature of 300-800℃ and a time of 1-6h; Preferably, this method does not use organic titanium-containing reagents.
10. The method according to claim 5 or 6, wherein, In step (4), the conditions for the second calcination include: a temperature of 100-700℃ and a time of 1-6h; Preferably, in step (4), the conditions for the second calcination include: a temperature of 200-700℃ and a time of 2-4h; Preferably, the amounts of Group VIII and Group VIB metal elements are such that, based on the total amount of the catalyst and in terms of oxides, the content of the Group VIII metal element is 0.5-10% by weight, preferably 1.5-5% by weight; and the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight. Preferably, the Group VIII metallic element is cobalt and / or nickel; Preferably, the Group VIB metal element is molybdenum and / or tungsten; Preferably, step (4) further includes: introducing an auxiliary agent, wherein the auxiliary agent is preferably selected from at least one of phosphorus, silicon, magnesium and fluorine; Preferably, the amount of the additive is such that the content of the additive in the prepared catalyst, based on the total amount of the catalyst and calculated as oxides, is 0.1-10% by weight. Preferably, in step (4), the amount of organic matter used is 0.2-10g based on carbon elements, compared to 100g of carrier.
11. The application of a catalyst according to any one of claims 1-4 or a catalyst prepared by the method according to any one of claims 5-10 in the deep hydrotreating of residual oil.
Citation Information
Patent Citations
Heavy distillate oil hydrotreating catalyst and application thereof
CN109833891A
Hydrogenation catalyst, preparation method and application thereof
CN113649016A